ABOUT SOME AMBIGUOUS TENDENCIES IN RUSSIAN HIGHER SCHOOL - Ekaterina A. Spiridonova (Высшее образование в России)
Abstract. The paper analyzes some contradictory tendencies in the development of higher chool in Russia. On the example of the Economics faculty of Saint Petersburg State University the author identifies some disturbing consequences of reforms, which are topical also for other higher educational institutions. On the basis of the questionnaire poll of BSC and MSC students, the author determines the key problems of higher school development on the modern stage. Inter alia the following questions are discussed: should master’s programs be academic or applied; is it rational to combine students after profile baccalaureate with students without appropriate education within the master course; is it reasonable to staff the state examination board entirely with business representatives. The paper presents the assessment of quality from graduates’ point of view. Some measures of improving the quality of education are suggested.